A Systematic Review on the Academic Stresses of College Students in Blended Instruction - Ortega, Fryzyl Zhneva N.; Suarez, Christine Jean; Yuipco, Wilynda A.; Cabanilla Jr., Angelito (RADJA PUBLIKA, 2023)
This meta-synthesis attempts to identify the stresses concerning college students' blended-learning environments and to synthesize the coping strategies they use to deal with stress in various cultural contexts. Out of 200 initial studies gathered using the Publish or Perish software, 50 articles were included. The selected studies were organized using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram. Using Braun and Clarke’s six-step thematic analysis, the synthesized data were analyzed which have emerged three themes, namely: concerns, challenges, and coping mechanisms. Results indicated that students' stress levels, whether in a face-to-face or hybrid setting, negatively impacted their academic performance. The lack of Information and Communication Technology (ICT) skills, restricted computer access, and spending a lot of time on screen make students more anxious. The rapid transition from face-to-face involvement to a blended learning environment negatively influences their perception of their academic efforts. It is recommended that various actions should be considered to lessen students’ stress and enhance the online learning process.